Clinical Landscape of Littoral Cell Angioma in the Spleen Based on a Comprehensive Analysis - Wang, Weijie; Qi, Guangzhao; Zhao, Xiangtian; Zhang, Yanping; Zhu, Rongtao; Liang, Ruopeng; Sun, Yuling (Frontiers in Oncology, 2022)
Abstract Objective: Littoral cell angioma (LCA) is currently considered to be a rare splenic tumor with malignant potential. As the epidemiology, pathogenesis, clinical manifestation, treatment, and prognosis remain unclear, the clinical diagnosis and treatment of LCA have not been standardized. Hence, we performed a comprehensive analysis of 189 observational studies comprising 435 patients to improve the current status of diagnosis and treatment. Methods: PubMed, Embase, WanFang and CNKI were searched from inception to May 2021 to identify LCA studies that were published in English and Chinese. The clinical information of LCA patients were extracted and analyzed. Results: The LCA has a male-to-female ratio of 0.90 and a solitary-to-multiple ratio of 0.31. In terms of clinical features, 69.7% of the patients showed splenomegaly, 49.7% were asymptomatic, and 39.2% experienced epigastric discomfort. As the imaging findings of patients with LCA were nonspecific, an image-guided biopsy (10/12) was a safe and effective method for diagnosing in this condition. Notably, results of the prognostic analysis indicated that LCA has a lower risk of recurrence and metastasis. The patient may develop a stable disease or the tumor will grow but will not metastasize. Besides, the novel immunohistochemical pattern of LCA was described as CD31+/ERG+/FVIII Antigen+/CD68+/CD163+/lysozyme+/CD8−/WT1−. Conclusion: LCA should be reconsidered as a benign primary splenic vascular neoplasm, which is more like an intra-splenic manifestation of abnormal body function. Image-guided biopsy with follow-up might be a beneficial choice for LCA patients. For LCA patients with abdominal discomfort, pathological uncertainty or continuous tumor enlargement, splenectomy remains the preferred treatment.